The Role of Geographic Systematic Information in Producing the Digital Elevation Model for Misan Governorate - Murtadha Mudhefer Sahar Al-Kaabi ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
Modern technologies are the cornerstone of many applications circulating nowadays, in particular the study of satellite data and ground cover, consisting of topographic or three-dimensional analysis of the surface of Misan Governorate 2022. The digital representation (DEM digital elevation model) gives a significant role in preparing the basic and required information that is used in GIS data, accordingly the topographic mapping of a series of cells and each cell has a known height through which topographic variations of the areas of study can be calculated. The research relied on the method of temporal-spatial analysis, remote sensing software, and geographic information systems. The paper concluded a number of results, including the extraction of contour lines for Misan Governorate in 2D dimensions, as well as the extraction of the digital elevation model in the form of 3D of the topographic surface of the area.